Panofsky on Physics, Politics, and Peace Pief Remembers - Panofsky, Wolfgang K.H (Springer New York : Imprint: Springer, 2007)
Wolfgang K.H. Panofsky is a prominent physicist who has been an active contributor to elementary particle physics, accelerator building, and laboratory administration as well as to international security policy and arms control. This volume is a somewhat unorthodox memoir. In Panofsky's words: "This volume contains an unsystematic account of my past work; it is not intended to be an autobiography in the conventional meaning of the term. It is not even remotely a scholarly description of the momentous developments in which I was able to participate; rather it is a recital of memorable episodes, borrowing from the compulsory preface of facetious British history: 'History is not what you thought. It is what you can remember.' " Pief.